Philosophers of consciousness: Polanyi, Lonergan, Voegelin, Ricoeur, Girard, Kierkegaard - Webb, Eugene (University of Washington Press, 1988)
Cover -- Contents -- Preface -- Introduction -- 1. Michael Polanyi: Consciousness as Focal and Subsidiary Awareness -- 2. Bernard Lonergan: Consciousness as Experience and Operation -- 3. Eric Voegelin: Consciousness as Experience and Symbolization -- 4. Paul Ricoeur: Consciousness as a Hermeneutic Field -- 5. René Girard: Consciousness and the Dynamics of Desire -- 6. Søren Kierkegaard: Consciousness as Incarnate Subjectivity -- 7. The Differentiation and Integration of Consciousness in the Individual and in History -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z.